Prevalencia de parásitos gastrointestinales en los ovinos de la provincia de Tungurahua. - Tisalema Shaca, Miguel Orominavi (2023)
The objective of the research was to determine the prevalence of gastrointestinal parasites (PGI) that affects sheep in the Tungurahua Province. The methodology used is through the coproparasitic analysis of 222 stool samples taken to establish the type and quantity of PGI present in the samples and the application of the FAMACHA technique and to be able to determine the health status of the animals. 10 types of parasites are identified with a prevalence rate of 74.77%; where the Creole race presents a greater number of cases (83.51%) in relation to the mestizo and merino; Also, the prevalence rate of PGI is higher in males (79.71%), while the analysis by age identifies a higher prevalence in sheep from 1 to 6 months (76.36%) and older than one year (77.55). %); Eimeria spp being the pathogenic organism with the greatest presence in sheep diagnosed with presence in 38.95% of sheep. The analysis of the FAMACHA method as a determinant of a level of anemia and therefore level of parasitism with Eimeria among the most prevalent parasites, determines that the method is not effective for this parasite, although it classifies 45% of sheep with risky anemia. and severe anemia.